Chemoradiotherapy response in recurrent rectal cancer. (16th December 2013) - Yu, Stanley K. T.; Bhangu, Aneel; Tait, Diana M.; Tekkis, Paris; Wotherspoon, Andrew; Brown, Gina
Abstract The efficacy of response to preoperative chemoradiotherapy (CRT) in recurrent versus primary rectal cancer has not been investigated. We compared radiological downsizing between primary and recurrent rectal cancers following CRT and determined the optimal size reduction threshold for response validated by survival outcomes. The proportional change in tumor length for primary and recurrent rectal cancers following CRT was compared using the independent sample t‐test. Overall survival (OS) was calculated using the Kaplan–Meier product limit method and differences between survival for tumor size reduction thresholds of 30% (response evaluation criteria in solid tumors [RECIST]), 40%, and 50% after CRT in primary and recurrent rectal cancer groups. A total of 385 patients undergoing CRT were analyzed, 99 with recurrent rectal cancer and 286 with primary rectal cancer. The mean proportional reduction in maximum craniocaudal length was significantly higher for primary rectal tumors (33%) compared with recurrent rectal cancer (11%) (P < 0.01). There was no difference in OS for either primary or recurrent rectal cancer when ≤30% or ≤40% definitions were used. However, for both primary and recurrent tumors, significant differences in median 3‐year OS were observed when a RECIST cut‐off of 50% was used. OS was 99% versus 77% in primary and 100% versus 42% in recurrent rectal cancer (P = 0.002 and P = 0.03, respectively). Only patients that demonstrated >50% size reduction showed a survival benefit. Recurrent rectal cancer appears radioresistant compared with primary tumors for tumor size after CRT. Further investigation into improving/intensifying chemotherapy and radiotherapy for locally recurrent rectal cancer is justified.